Strengthening ESP in Education 4.0 - Widyaningrum, Agnes (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The disruption technology impacts industrious educational setting empowering more skills than knowledge. The online learning is another thing to do by the institutional education while the content of the learning materials reflect the learnersâ need. The emergence of CLT led to the need of using English in more specific use such as for occupational or educational framework. Some studies deal with ESP focusing on teaching some specific kinds of language and communicative skills needed for particular roles rather than concentrate on more general English (Richards, 2006:12). The advance technology in teaching began when the internet dominates the humanâs life. ICT offers a solution for educational institution to deliver their teaching and learning process nowadays. The online learning will give more impacts for language learners as they belong to millennium generation. Teachers should be aware of this because ICT is an important part of the development of teaching and learning (Wyse, Dominic et.al., 2008:237). Therefore teachers should use ICT as their tool to enhance their teaching and learning practices. This study concerns to develop 4.0 English curriculum by strengthening ESP using ICT in English classroom context.